TOWARDS AN ISLAMIC SPIRITUALITY-BASED FRAMEWORK FOR PUBLIC ACCOUNTANTS' ETHICS - Nursanty, Ida Ayu; Lestari, Baiq Anggun Hilendri; Jumaidi, Lalu Takdir; Wardani, Rosyia; Prathama, Baiq Desthania (Jurnal Aplikasi Akuntansi, 2026)
The accounting profession continues to face ethical challenges due to recurring financial scandals and the increasing complexity of digitalized auditing. This study aims to construct the ethics of public accountants from the perspective of Islamic spirituality, emphasizing akhlakul karimah (noble character) as the foundation for professional conduct. Adopting a qualitative phenomenological approach with literature-based analysis, the research employs spiritual practices such as dhikr, prayer, and contemplative reflection (tafakkur) as analytical instruments to explore the balance of reason, justice, honesty, and love in professional ethics. Data interpretation is conducted through reflective discourse analysis, allowing the integration of spiritual insights into ethical frameworks. The findings reveal that public accountants who embody these virtues cultivate a humane identity as God's stewards (khalifah), integrating spiritual awareness into ethical decision-making and professional responsibility. Such accountants not only uphold compliance but also promote love, social justice, and environmental stewardship, aligning their practice with a higher form of accountability. The novelty of this study lies in formulating a transformative ethical model that operationalizes Islamic spiritual practices into concrete analytical instruments, extending beyond previous spirituality-based ethics research. This contribution offers implications for accounting education, professional regulation, and the advancement of sustainable and ethically responsible accounting practices.